A Study on Factors Affecting Consumption of Organic Tea: Evidence from Consumers in Kathmandu Valley - Ojha, Gaurav; Shakya, Upama (Nepalese Journal of Management Science and Research, 2019)
This study examines the factors affecting consumption of organic tea with evidence from organic tea consumers in Kathmandu Valley. In this study, purchase intention for consuming organic tea is the dependent variable, whereas health benefits, environmental concerns, together with taste and price are considered as independent variables. The study has utilized different types of non-probability sampling procedures to locate 50 regular organic tea consumers within Kathmandu valley. Since, the study on purchase intention regarding organic tea product is a relatively new phenomenon, hence this study is exploratory in its orientation. In this study descriptive analysis, together with Chi-Square results and correlation coefficients have been computed to examine nature, direction and significance of the relationship between selected factors and purchase intention for consuming organic tea. Results indicate that purchase intention of customers towards organic tea product is associated with perceived health benefits and environmental concerns. Besides, consumers are willing to pay higher price to consume organic tea when they perceive significant health benefits even with non- preferable taste of organic tea products. Furthermore, marketing implications of data analysis and findings have been comprehensively elaborated in this study. And, more importantly, in regards to sustainable consumption patterns, as SDG-12 indicates, this study indicates that consumers in Kathmandu Valley are prepared for responsible consumption as they perceive environmental and health benefits in a given product.